Economicharity and New Media Authority: the Piety and New Spiritualism of Philanthropists in 21st Century - Lukis Alam; Ogi Dani Sakarov; Aminah (Universitas Ahmad Dahlan, 2021)
Economicharity is a discourse that is always being talked about, on the different side its existence has become a trend in the 21st era. Implementatively, economicharity is realized by philanthropic actions carried out by all levels of society and this has become a global phenomenon that is spreading throughout the world. With the rapid development of information technology, philanthropy can now be done using internet media. In the meantime, the virtual era is marked by an increase in speed and acceleration in the process of information and communication that allows people to connect with each other into the network. Fundraising becomes an activity that promotes the spirit of togetherness, mutual respect for each other. This research seeks to elaborate and explore philanthropic actions carried out by sedekahrombongan.com, kitabisa.com, dompetdhuafa.com. This research is a qualitative study conducted with a virtual ethnographic. It is hoped that this research will uncover the tendency of a philanthropic institution to use internet media as a breakthrough model in promoting economicharity globally. On the different side, the development of philanthropic institutions in Indonesia gave rise to a different orientation among them, the awareness of popularizing humanitarian attitudes had made these institutions synergized with similar institutions owned by the government. In addition, this research will deeply observe netizens in interacting with these institutions.